Utility of Palladium as a Catalyst for the Synthesis of Five and Six-Membered Heterocyclic Moieties - Singh, Saumya; Kumar, Rajnish; Tripathi, Shrishti; Salahuddin; Mazumder, Avijit; Singh, Nardev (Current Organic Chemistry, 2026)
Heterocyclic chemistry is crucial, representing approximately fifty percent of all established organic compounds. Five and six-membered heterocyclic moieties such as pyrrole, thiazole, imidazole, oxadiazole, pyridine, piperazine, and pyrimidine have been reported with a wide range of pharmacological activities. In modern chemistry, palladium-catalyzed reactions have emerged as a powerful tool for synthesizing different heterocyclic moieties, as they provide high stereoselectivity and regioselectivity. Palladium is an effective, environmentally friendly, and cost-effective metal with diverse scopes in organic synthesis. It offers efficient and precise methods for developing diverse molecular structures and potential drug molecules. Palladium-catalyzed reactions comprised C-C cross-coupling, C-N cross-coupling, C-H activation, cyclization, etc. The present manuscript provides insights into recently reported methods for the synthesis of 5 and 6-membered heterocyclic moieties where palladium was utilized as a catalyst.
Keywords: heterocycle compound